EFFECT OF THE ROTATING BLADES ON THE STABILITY OF FLOATING WIND TURBINE - SYED ZAINUDIN, SYED AMIR ADAM (Universiti Teknologi PETRONAS, 2017)
ABSTRACT: The objectives of the proposed study is to study the effect of rotating blades on the stability of floating wind turbine. The rotating blades or can be called as gyromotion effect had resulted in various of effect towards the stability of floating wind turbine such as that can be seen with human eyes are pitch, yaw, surge, roll, sway and heave, the paper will briefly summarise the background of floating wind turbine and the methodology used to analyse and compute the effect of rotating blade or gyromotion towards the stability of floating wind turbine by using a simulation software which is Star CCM that can simulate the real life time event in order to analyse the effect of the rotating motion towards the stability of the structure. The data used in the study will be from previous researches that have been made.